Empowerment of Micro Small Medium Enterprises in Urban Economic Growth in Makassar - Thamrin Abduh; Ridwan; Hamzah Fansury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Micro, small, and medium enterprises (MSMEs) are one of the main pillars of the national economy, with an independent perspective and great potential to improve welfare. This study aims to determine the form of empowerment that is carried out to MSMEs as an effort to improve the welfare of business owners in Makassar City, as well as the response of business owners related to the empowerment program that has been carried out by the local government, especially through the Cooperatives and MSMEs Service in Makassar. The population in this study is all business owners in Makassar, both those who have participated in empowerment programs from the government and those who have never participated in these programs. The sample in this study was 60 business people selected by purposive sampling by considering several criteria, both the type of business and the background of the business owner, so that the respondents in this study could be heterogeneous. In addition, interviews were conducted with academics. Research instruments are in the form of questionnaires and interview guidelines. The data were analyzed descriptively and qualitatively. The results showed that: 1) empowerment programs desired by business owners tended to lead to improvements in the quality of business products; and 2) empowerment programs focused on product marketing training. 2) Recommendations related to the results of research, namely: a) Every empowerment program to be carried out by the government should be prepared based on an analysis of the needs of the beneficiaries, in this case, business owners. b) Empowerment programs carried out by the government should be directed at improving the quality of business products, providing training in marketing products, or providing containers to business people to market their business products. c) The program held should be able to socialize well and evenly with all business owners. This can be achieved whenever information from the government is easily accessed by all businesses.